2014
DOI: 10.1161/circinterventions.113.001135
|View full text |Cite|
|
Sign up to set email alerts
|

Trial Occlusion to Assess the Risk of Persistent Pulmonary Arterial Hypertension After Closure of a Large Patent Ductus Arteriosus in Adolescents and Adults With Elevated Pulmonary Artery Pressure

Abstract: Background-No method is available to predict whether patients with patent ductus arteriosus (PDA) and severe pulmonary arterial hypertension (PAH) will show persistent postprocedural PAH (PP-PAH) after PDA closure. This study evaluated the usefulness of trial occlusion for predicting PP-PAH after transcatheter PDA closure in patients with severe PAH. Methods and Results-Trial occlusion was performed in 137 patients (age ≥12 years) with PDA and severe PAH. All patients undergoing trial occlusion had a mean pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Postocclusion pulmonary artery systolic pressures more than half of aortic systolic pressures have been identified to be a predictor of persistent PAH after complete device occlusion in hypertensive ducts. [ 4 ] The pulmonary artery pressures may be very labile in patients who have airway issues, respiratory infection and on agitation and exercise. Such labile episodes may predispose to suprasystemic pulmonary artery pressures and aortic embolization of the occluder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postocclusion pulmonary artery systolic pressures more than half of aortic systolic pressures have been identified to be a predictor of persistent PAH after complete device occlusion in hypertensive ducts. [ 4 ] The pulmonary artery pressures may be very labile in patients who have airway issues, respiratory infection and on agitation and exercise. Such labile episodes may predispose to suprasystemic pulmonary artery pressures and aortic embolization of the occluder.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] Test occlusion of the PDA with balloon or occluder device is often utilized in the catheterization laboratory to decide operability of large hypertensive ducts. [ 3 4 ] In patients, who demonstrate clear left to right flows on echocardiography across the ducts and lack of oxygen desaturation in lower limbs, if the pulmonary artery pressure shows a significant fall and separation from aortic pressure, the ducts are considered operable. These patients may still need to be continued pulmonary vasodilators.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evaluation process was simplified and the nature of pulmonary hypertension was determined directly by trial occlusion. When the pulmonary systolic pressure was reduced > 25% after the PDA was occluded, we concluded that the patient had dynamic pulmonary hypertension and interventional therapy was performed [2,12]. Iatrogenic descending aortic coarctation should be avoided.…”
Section: Intraoperative Experiencementioning
confidence: 97%
“…The inclusion criteria were as follows: age ≤ 36 months and PDA associated with moderate-to-severe pulmonary hypertension (pulmonary hypertension was determined by the ratio of pulmonary to aortic systolic pressure). Pulmonary and aortic systolic pressure were measured directly using a cardiac catheter before PDA occlusion (mild: 0.25-0.45; moderate: 0.46-0.75; severe: > 0.75) [2]. The exclusion criteria were other cardiovascular malformations that required simultaneous treatment and cardiac insufficiency or Eisenmenger syndrome.…”
Section: Patientsmentioning
confidence: 99%
“…Pulmonary vascular disease characterized by histological changes consistent with severe, irreversible pulmonary vascular involvement may completely resolve after closure of PDA. Reactivity of pulmonary vascular bed to pulmonary vasodilating agents and/or significant reduction of pulmonary artery pressure and resistance during test occlusion [91] may offer reassurance with regard to reversibility, but the absence of such evidence does not exclude the possibility of reversibility in the long term. Closing the PDA without test occlusion is at a risk of right heart failure and hemodynamic collapse.…”
Section: Adult Pdamentioning
confidence: 99%